Anaesthetic management of caesearean section in a patient with severe uncorrected coarctation of aorta: A case report and literature review - Nitika Goel; Indumohini Sen; Banashree Mandal; Vadhan Prassana (Wolters Kluwer Medknow Publications, 2018)
Perioperative management of parturients with congenital heart disease is a challenge for the anaesthesiologist. The choice of anaesthetic technique plays an important role in determining the postoperative outcome of such patients. We report a 35 weeks primigravida diagnosed with coarctation of aorta in early pregnancy. She had normal antenatal course but at 35 weeks she presented with uncontrolled upper limb hypertension. She was planned for early elective caesarean section in view of presence of imment HELLP syndrome. Here, we discuss the anaesthetic challenges and their perioperative management leading to favourable outcome of the patient.